Financial Resilience as Mediator in ESG Risk Rating, Leverage and Profitability Toward Firm Value - Rini Mulyasari; Indra Siswanti (International Journal Labs, 2026)
This study examines the effects of ESG Risk Rating, leverage, and profitability on firm value, and tests whether financial resilience (Economic Value Added/EVA) mediates these relationships among firms in the IDX ESG Leaders index during 2020–2024. The study employs quantitative panel-data regression with purposive sampling and balanced panel observations. Model selection is conducted using Chow, Hausman, and Lagrange Multiplier (LM) tests. Mediation is tested using the Sobel test. ESG Risk Rating, leverage, and profitability significantly affect firm value. ESG Risk Rating and leverage significantly affect EVA, while profitability does not significantly affect EVA. EVA significantly affects firm value. Sobel results confirm that EVA mediates the effects of ESG Risk Rating and leverage on firm value, but does not mediate profitability’s effect on firm value. Financial resilience (EVA) functions as an intervening mechanism for ESG Risk Rating and leverage in explaining firm value in IDX ESG Leaders firms, while profitability influences firm value primarily through direct effects rather than via EVA.